The first four years - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : Harper & Row, 1971)
During their first four years of marriage, Laura and Almanzo Wilder have a child and fight a losing battle in their attempts to succeed at farming on the South Dakota prairie.
1 3 4 6 7 8 9 10 11 12 13 15 17 18 19 20 21 23 25 26 27 29 30 31 33 36 38
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Almanzo -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Wilder, Almanzo -- Fiction; Frontier and pioneer life -- Fiction; Frontier and pioneer life -- Fiction; South Dakota -- Fiction; South Dakota -- Fiction